We know a quadratic function in standard form is given by:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
where a, b and c are constants. To find the value of the constants we can use the points given.
For the point (-2,65) we have:
![\begin{gathered} (-2)^2a-2b+c=65 \\ 4a-2b+c=65 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dv3cbd4xes5adpimehc84rpgo72td1up8m.png)
For the point (0,165) we have:
![\begin{gathered} (0)^2a+(0)b+c=165 \\ c=165 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a3iwe4vnfhk8gsblu9aefwl45r8y3nvogr.png)
For the point (6,225) we have:
![\begin{gathered} (6)^2a+6b+c=225 \\ 36a+6b+c=225 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2wu3mje4hbj4vcvvaw0i61lelpm0awpgqs.png)
Hence we have the system of equations:
![\begin{gathered} 4a-2b+c=65 \\ 36a+6b+c=225 \\ c=165 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gayhsd3ym69o8fgp9zmtm1t3540vy04ju7.png)
Plugging the value of c in the first two equations we have:
![\begin{gathered} 4a-2b+165=65 \\ 36a+6b+165=225 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/npq5f8n2gehbyszvslpkcqb6mz1fck7zzo.png)
which leads to:
![\begin{gathered} 4a-2b=-100 \\ 36a+6b=60 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lvy2l7kz57lkqotrqlvjzt6dhedw9wj98q.png)
Multiplying the first equation by 3 we have:
![\begin{gathered} 12a-6b=-300 \\ 36a+6b=60 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4jldkpfou3aqdzs000zvizspuzaxjdkhor.png)
adding the equations we have that:
![\begin{gathered} 48a=-240 \\ a=-(240)/(48) \\ a=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rtdmgr1s1ak6ghmrbgdg733ub2ie5jkqe7.png)
Plugging the value of a in the equation above we have:
![\begin{gathered} 4(-5)-2b=-100 \\ -20-2b=-100 \\ 2b=100-20 \\ 2b=80 \\ b=(80)/(2) \\ b=40 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uk6dypvgzhho0sz4d0r031s4ixlyxlsdw3.png)
Once we know the values of the constants we conclude that the quadratic equation in standard form is:
![y=-5x^2+40x+165](https://img.qammunity.org/2023/formulas/mathematics/college/aoceebmf31m04q2lhalisr2r2f6fcu9iez.png)
Now, to write the equation in vertex form we need to complete the square on x:
![\begin{gathered} y=-5(x^2-8x)+165 \\ y=-5(x^2-8x+(-(8)/(2))^2)+165+5((8)/(2))^2 \\ y=-5(x-4)^2+245 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iwoqypo8f2vrxf203xxo31v0pdkcoyyqhr.png)
Therefore, the equation written in vertex form is:
![y=-5(x-4)^2+245](https://img.qammunity.org/2023/formulas/mathematics/college/ekwa4qlykthi2gmagdx2thejz2wc7h13uh.png)
Now, the unique features of the two forms presented are:
Standard form: The equation is expanded and reduced.
Vertex form: The vertex of the parabola is readily shown in the equation.